High-Performance flexible solid-state supercapacitor with an extended nanoregime interface through in situ polymer electrolyte generation - Anothumakkool, Bihag; Torris, Arun A. T.; Veeliyath, Sajna; Vijayakumar, Vidyanand; Badiger, Manohar V.; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2016)
{Here, we report an efficient strategy by which a significantly enhanced electrodeelectrolyte interface in an electrode for supercapacitor application could be accomplished by allowing in situ polymer gel electrolyte generation inside the nanopores of the electrodes. This unique and highly efficient strategy could be conceived by judiciously maintaining ultraviolet-triggered polymerization of a monomer mixture in the presence of a high-surface-area porous carbon. The method is very simple and scalable, and a prototype, flexible solid-state supercapacitor could even be demonstrated in an encapsulation-free condition by using the commercial-grade electrodes (thickness = 150 mu m
Keywords: cyclic voltametry; impedance analysis; in situ polymer generation; interface; polymer electrolyte; supercapacitor